Auditoria en seguridad vial al sector club campestre - el Caimo, vía Pereira Armenia abscisas 0+000 a 8+000 (2021)
The work carried out on carrying out a Road Safety Audit to the Club Campestre - El Caimo sector, via Pereira Armenia abscissa 00 + 000 - to 08 + 300, which was developed in this work, then with each of the specific objectives, to take it to After completing the tasks of each one of them, they established the critical points of accident, structure, elaboration and matrix obtained and risk maps, the signaling, containment barriers and geometric design of the road were analyzed, a bibliographic review of the from which the pertinent information was extracted for the state of the art and the theoretical framework that allows giving support from the theoretical-conceptual.